1988
DOI: 10.1542/peds.81.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Administration of Measles-Mumps-Rubella Vaccine With Booster Doses of Diphtheria-Tetanus-Pertussis and Poliovirus Vaccines

Abstract: The safety and efficacy of simultaneous administration of measles-mumps-rubella (MMR), diphtheria-tetanus-pertussis (DTP), and trivalent oral poliovirus (OPV) vaccines in a test group of 405 children were compared with the safety and efficacy of sequential administration of the same vaccines in a control group of 410 children given MMR followed by booster doses of DTP and OPV 2 months later. The study was double blind and placebo controlled with respect to DTP and OPV. Seroconversion rates to measles, mumps, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Studies of concomitant use are typically conducted when 2 vaccines are likely to be administered at the same time for programmatic efficiency. With only a few exceptions, seroconversion rates and adverse event frequency are not impacted by simultaneous administration of the most-commonly used live and inactivated vaccines [ 48 50 ]. One study has convincingly demonstrated that concomitant administration of Hecolin with another protein-based vaccine, hepatitis B, was both safe and did not adversely affect immune response to either vaccine [ 51 ].…”
Section: Barriers To Usementioning
confidence: 99%
“…Studies of concomitant use are typically conducted when 2 vaccines are likely to be administered at the same time for programmatic efficiency. With only a few exceptions, seroconversion rates and adverse event frequency are not impacted by simultaneous administration of the most-commonly used live and inactivated vaccines [ 48 50 ]. One study has convincingly demonstrated that concomitant administration of Hecolin with another protein-based vaccine, hepatitis B, was both safe and did not adversely affect immune response to either vaccine [ 51 ].…”
Section: Barriers To Usementioning
confidence: 99%
“…With some exceptions, simultaneously administering the most widely used live and inactivated vaccines has produced seroconversion rates and rates for adverse reactions similar to those observed when the vaccines are administered separately (10)(11)(12)(13). Routine administration of all age-appropriate doses of vaccines simultaneously is recommended for children for whom no specific contraindications exist at the time of the visit.…”
Section: Simultaneous Administrationmentioning
confidence: 99%